FRI0618 Concordance with latest guidelines for dmard screening and monitoring in secondary care. (12th June 2018) - Cefai, E.; Xhaxho, D.; Mercieca, C.; Borg, A.
Abstract : Background: DMARDs need to be prescribed safely. Screening and monitoring for toxicity is essential when using these medications. The British Society of Rheumatology (BSR) has recently published guidance on screening and monitoring of non-biologic DMARDs. Objectives: The aim of this audit was to assess current practice on synthetic DMARD screening and monitoring within our rheumatology department, in a secondary care setting, using the BSR 2017 guidelines as the standard of care. Methods: 81 consecutive adult patients who were started on synthetic DMARDs in 2016 were recruited. The data required was collected from case notes and isoft clinical manager after obtaining data protection clearance. DMARDs included Hydroxychloroquine (HCQ), Methotrexate (MTX), Sulfasalazine (SSA), Azathioprine (AZA) and Leflunomide (Lef). Baseline screening was assessed by checking for documentation of height, weight, baseline blood tests including virology and documentation of known lung disease and smoking with the relevant investigations when necessary. Specialist nurse referral and content of consultation was assessed for discussion regarding fertility/pregnancy when relevant, intercurrent illnesses and vaccinations. Drug-specific screening and monitoring included folic acid prescription (FA) for MTX, TPMT testing for AZA, ophthalmic review for HCQ as well as weight and blood pressure (BP) monitoring for Lef. Finally all patients were checked for regular blood monitoring at weeks 2, 4, 6 and every 3 months thereafter with the exception of SSA & HCQ monotherapy. Calibri (Body) Results: Weight and height were not documented in 50.6% and 66.7% of patients respectively. Baseline blood tests were present in all but 1 patient with the exception of virology. The latter was present in 6.2% of cases only. Smoking status was assessed in 92.6% of cases. CXR and pulmonary function tests were warranted for 9 patients but were only done in 4 cases. 98.8% of patients were referred to the specialist nurse for DMARD education. Discussion on fertility and pregnancy, where applicable, was discussed in 95% of cases, vaccinations in 97.5% of cases and advice regarding management of intercurrent illnesses in 2.5% of cases. Drug monitoring at 2, 4 and 6 weeks was done in 33.3%, 90.1% and 80.2% of cases respectively. BP and weight were checked for all patients on Lef whilst blood monitoring for SSA monotherapy persisted after 1 year in 80% of cases. Drug specific recommendations including FA prescription, TPMT testing and ophthalmic reviews were done in all patients. Conclusions: This audit showed a high level of concordance with the BSR monitoring guidelines for synthetic DMARDs. Aspects that require improvement have been highlighted. By ensuring that there is proper documentation of all aspects pertaining to the work-up prior to starting a patient on a DMARD, one can then introduce screening and monitoring schedules targeted at the prevention and early detection of adverse treatment outcomes. Disclosure of Interest: None declared